2015
DOI: 10.1158/1940-6207.capr-14-0371
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of VDR Expression in Apc-Mutant Mice, Human Colon Cancers and Adenomas

Abstract: One variable that may impact the ability of vitamin D to reduce colon cancer risk is the expression of its high affinity receptor, VDR. Here we show that vitamin D does not reduce tumor formation in ApcΔ14/+ mice and that VDR expression is lost in the majority of the colon tumor cells. The extent of VDR loss corresponded inversely to the level of β-catenin nuclear localization and could be observed in early lesions composed of just a few crypts. Analysis of reported VDR regulators showed that the repressing cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 72 publications
1
20
0
Order By: Relevance
“…Enrichment for binding sites of VDR, which belongs to the Thyroid hormone receptor-related factor (NR1) family, was also detected in the intersection. It has been suggested that vitamin D has no effect on tumor reduction in APC-deficient mice and that VDR expression is lost in the majority of the colon cancer cells (Giardina et al, 2015 ). Interestingly, the analysis also revealed enrichment for binding sites of β-catenin which interacts as a cofactor with members of the TCF-7-related factor family to activate Wnt target gene expression (see Supplementary Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Enrichment for binding sites of VDR, which belongs to the Thyroid hormone receptor-related factor (NR1) family, was also detected in the intersection. It has been suggested that vitamin D has no effect on tumor reduction in APC-deficient mice and that VDR expression is lost in the majority of the colon cancer cells (Giardina et al, 2015 ). Interestingly, the analysis also revealed enrichment for binding sites of β-catenin which interacts as a cofactor with members of the TCF-7-related factor family to activate Wnt target gene expression (see Supplementary Table S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, others have found that VDR mRNA or protein levels are reduced in human colon tumors (7,28) and other cancers (2931) . Forty percent of colon tumors have mutations in the K-RAS gene (9) and previous research has shown that RAS activating mutations suppress 1,25(OH) 2 D action in some cells (1012,3234) but enhance 1,25(OH) 2 D action in MG-63, HeLa, and COS-1 kidney cells (33,35) .…”
Section: Discussionmentioning
confidence: 99%
“…The proximal promoter region of the VDR gene is hypermethylated in breast cancer cell lines (21) and some adrenocortical carcinomas (40) . In addition, inhibition of DNA methylation using 5′-aza-2′-deoxycytidine increased VDR expression and 1,25(OH) 2 D-mediated growth arrest in breast cancer cell lines (21) and VDR expression in HT-29 colon cancer cells (7) . In contrast, Habano et al (41) reported that inhibition of DNA methylation had no effect on VDR mRNA expression in several colon cancer cell models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the kidney is the main source of serum 1,25D 3 levels, the extra-renally synthesized 1,25D 3 , which acts locally in an autocrine and paracrine manner, is an indispensable source for the cancer-preventive action of vitamin D. However, during tumor development the expression of the different molecules of the vitamin D system in the affected tissue becomes deregulated. In undifferentiated colorectal adenocarcinomas not only CaSR expression, but also expression of VDR and CYP27B1 is lower than in differentiated tumors (Bareis et al, 2002 ; Bises et al, 2004 ; Giardina et al, 2015 ). Whether these phenomena are linked or not, needs to be determined.…”
Section: Effect Of the Casr On Expression Of The Vitamin D Systemmentioning
confidence: 99%